Объяснение:
1) Решениеy=(4·x-9)^5
((4·x-9)^5)' = 20(4·x-9^)4
Поскольку:
((4·x-9)5)' = 5·(4·x-9)^5-^1((4·x-9))' = 20(4·x-9)^4
(4·x-9)' = 4
20(4·x-9)^4
y=(x2-3x+1)7
2) Решение:((x2-3x+1)7)' = (-7·3x·ln(3)+14·x)(x2-3x+1)6
Поскольку:
((x2-3x+1)7)' = 7·(x2-3x+1)7-1((x2-3x+1))' = (-7·3x·ln(3)+14·x)(x2-3x+1)6
(x2-3x+1)' = (x2)' + (-3x)' + (1)' = 2·x + (-3x·ln(3)) = -3x·ln(3)+2·x
(x2)' = 2·x2-1(x)' = 2·x
(x)' = 1
Здесь:
Решение ищем по формуле:
(af(x))' = af(x)*ln(a)*f(x)'
(-3x)' = -3x·ln(3)(x)' = -3x·ln(3)
(x)' = 1
(-7·3x·ln(3)+14·x)(x2-3x+1)6
3) Решение:y=(sin(x))^3
(sin(x)^3)' = 3·sin(x)^2·cos(x)
Поскольку:
(sin(x)^3)' = 3·(sin(x))^3-1((sin(x)))' = 3·sin(x)^2·cos(x)
(sin(x))' = cos(x)
3·sin(x)2·cos(x)
1y-0.5-0.5+0.2y+1=0
1.2y=0
y=0
ответ: 0
2) (x² +3x+2)(x² +3x+4)=8
(x² +3x+2)(x² +3x+2+2)=8
y=x² +3x+2
y(y+2)=8
y² +2y-8=0
D=4+32=36
y₁=(-2-6)/2= -4
y₂=(-2+6)/2=2
При у= -4
x² +3x+2= -4
x² +3x+2+4=0
x² +3x+6=0
D=9-24<0
нет решений.
При у=2
x² +3x+2=2
x² +3x+2-2=0
x² +3x=0
x(x+3)=0
x=0 x+3=0
x= -3
ответ: -3; 0.
3) (x² -2x-3)(4-x² +2x)= -2
(x² -2x-3)*(-(x² -2x-4))= -2
(x² -2x-3)(x² -2x-3-1)=2
y=x² -2x-3
y(y-1)=2
y² -y-2=0
D=1+8=9
y₁=(1-3)/2= -1
y₂=(1+3)/2=2
При у= -1
x² -2x-3= -1
x² -2x-3+1=0
x² -2x-2=0
D=4+8=12
x₁=(2-√12)/2=(2-2√3)/2=1-√3
x₂=1+√3
ответ: 1-√3; 1+√3
4) (x² -x-11)(x² -x-21)= -9
(x² -x-11)(x² -x-11-10)= -9
y=x² -x-11
y(y-10)= -9
y² -10y+9=0
D=100-36=64
y₁=(10-8)/2=1
y₂=(10+8)/2=9
При у=1
x² -x-11=1
x² -x-11-1=0
x² -x-12=0
D=1+48=49
x₁=(1-7)/2= -3
x₂=(1+7)/2=4
При у=9
x² -x-11=9
x² -x-11-9=0
x² -x-20=0
D=1+80=81
x₁=(1-9)/2= -4
x₂=(1+9)/2=5
ответ: -4; -3; 4; 5.